2021
DOI: 10.1101/2021.05.13.21254848
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identifying Patterns of ALS Progression from Sparse Longitudinal Data

Abstract: Amyotrophic Lateral Sclerosis (ALS) is a neurodegenerative disease that is complex in its onset, pattern of spread, and disease progression. The heterogeneity of ALS makes it extremely challenging to determine if a disease modifying therapy is effectively slowing progression. While accurately modeling ALS progression is critical to developing therapeutics, current computational methods fail to capture the complexity of disease progression. We aimed to robustly characterize disease progression patterns in ALS. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 38 publications
1
12
1
Order By: Relevance
“…9,10 At the same time, scores can improve with symptomatic therapy despite disease progression. 9,11 Though the ALSFRS-R is not a true PRO, efforts to reword and use the ALSFRS-R as a self-entry scale (ALSFRS-RSE) show strong agreement between the ALSFRS-R and ALSFRS-RSE. 7,12 Work is underway to develop digital quantitative outcome measures for use in ALS clinical trials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,10 At the same time, scores can improve with symptomatic therapy despite disease progression. 9,11 Though the ALSFRS-R is not a true PRO, efforts to reword and use the ALSFRS-R as a self-entry scale (ALSFRS-RSE) show strong agreement between the ALSFRS-R and ALSFRS-RSE. 7,12 Work is underway to develop digital quantitative outcome measures for use in ALS clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…Pooled clinical trial data of 3132 people with ALS (PALS) showed that 25% of trial participants do not experience progression on ALSFRS‐R over 6 mo 9,10 . At the same time, scores can improve with symptomatic therapy despite disease progression 9,11 . Though the ALSFRS‐R is not a true PRO, efforts to reword and use the ALSFRS‐R as a self‐entry scale (ALSFRS‐RSE) show strong agreement between the ALSFRS‐R and ALSFRS‐RSE 7,12 …”
Section: Introductionmentioning
confidence: 99%
“…Amyotrophic lateral sclerosis (ALS) carries a uniformly poor prognosis with a median survival of 2–5 years after onset 1 . However, individual patient disease trajectories vary widely 2 . Variability in the rate of ALS progression remains poorly understood, poses a major hurdle for clinical trial design and interpretation, and limits clinicians' ability to counsel patients.…”
mentioning
confidence: 99%
“…Variability in the rate of ALS progression remains poorly understood, poses a major hurdle for clinical trial design and interpretation, and limits clinicians' ability to counsel patients. Moreover, clinical progression, as commonly assessed by the Revised ALS Functional Rating Scale (ALSFRS‐R), does not occur in a linear manner as once assumed 2,3 . There is an unmet need for biomarkers of ALS disease activity and progression, which Vu and colleagues seek to address in the current issue 4…”
mentioning
confidence: 99%
See 1 more Smart Citation